A proposta política de um município para a inclusão escolar: um tema, vários olhares. - Fragelli, Patrícia Maria (2005)
The general aim of the present study was to investigate how the current public policies of educational inclusion have been translated by different educational agents, inserted in the context of regular education. We attempted at interpreting a same theme: educational inclusion policies , through the eyes of several educational agents. The research was made at municipal schools, during the administrative period between the years of 2001 and 2004. It was a qualitative research kind, in which the following subjects participated: two elementary school teachers, cycle I ( 3rd and 4th grades); an elementary municipal school director; an educational therapist who worked for the Municipal Education Office, with children considered in high risk situation; a pedagogy specialist, member of the State Education Office, who worked with minority groups inclusion, specially black minorities; and an educational therapist, responsible for the special education area, in the State Education Office. The theoretical approach on which this research was based on regarded the production of teachers knowledge and the investigations which try to understand the teacher s practical thought, his/her values, believes and reflective capacity. The data collecting procedures were divided into four steps: questionnaire application; interviews; observations and documental analysis. This study did not intend to provide ready to make recipes or elaborate a manual on how to handle inclusion; on the contrary, we tried to better understand how the established policies in theoretical terms have been made effective in the practical context and which feelings, perceptions and difficulties are faced by the ones who experienced it in their every day lives. The data collection and analysis allowed us to better understand the issue investigated, giving voices to the ones directly involved in the process, as well as provided interesting information to new research, supplying meaningful data which can be considered in the effective proposal for inclusive education. The main results obtained indicate that the different educational agents have different views on inclusive education policies, which make their actions distinctive. While administrators (members of the State Education Office) see some possibilities and no difficulties in the translation of the established policies, the teachers signed with a feeling of not being prepared and of difficulty in executing their role as professionals with an inclusive posture. We verified also the necessity of reevaluating the teaching degree courses, contemplating in their curricular framework disciplines related to the inclusion. Through this investigation it was possible to verify that all the subjects established rich and meaningful criteria in the attempt to understand and favor the inclusive process.